2019
DOI: 10.1521/pedi.2019.33.5.623
|View full text |Cite
|
Sign up to set email alerts
|

Forms, Importance, and Ineffability of Factor Interactions to Define Personality Disorders

Abstract: The emergent interpersonal syndrome (EIS) approach conceptualizes personality disorders as the interaction among their constituent traits to predict important criterion variables. We detail the difficulties we have experienced finding such interactive predictors in our empirical work on psychopathy, even when using uncorrelated traits that maximize power. Rather than explaining a large absolute proportion of variance in interpersonal outcomes, EIS interactions might explain small amounts of variance relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…that affect power. The simulation results underscore what researchers have previously highlighted—statistical interactions will be difficult to detect (Benning & Smith, 2019; McClelland & Judd, 1993). Though the PPI-R and TriPM are two of the more popular measures of psychopathy, research using other popular measures of psychopathy has found little evidence of interactive effects.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…that affect power. The simulation results underscore what researchers have previously highlighted—statistical interactions will be difficult to detect (Benning & Smith, 2019; McClelland & Judd, 1993). Though the PPI-R and TriPM are two of the more popular measures of psychopathy, research using other popular measures of psychopathy has found little evidence of interactive effects.…”
Section: Discussionsupporting
confidence: 71%
“…Interactive effects may become more relevant in the absence of main effects, as is the case for traits related to boldness. Nonetheless, Benning and Smith (2019) highlighted that if the source of impairment in emergent interpersonal syndromes is due to the interaction among traits, one would expect large interaction effect sizes (for both two-way interaction as well as three-way interactions concerning psychopathy) that runs against the empirical realities surrounding interactive effects and the empirical results within the psychopathy literature.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of EIS postulates that the relation between psychopathy’s constituent facets is of a multiplicative rather than an additive nature. Although it is methodologically challenging to detect such statistical interactions between the dimensions of psychopathy (Benning & Smith, 2019), our results can help to generate more precise hypotheses for these interactions and their forms in order “to maximize the chances of detecting EISs” (Benning & Smith, 2019, p. 631).…”
Section: Discussionmentioning
confidence: 95%
“…A second issue with the APRT trials is that each of the 64 trials represents a unique combination of the within-subject manipulations. This means that more complex interaction effects may exist, which were not examined due to the difficulty (if not impossibility) of conceptually explaining them in ecologically useful terms and the lack of necessary power to discern these effects [ 66 ]. Adding additional trials so that each combination of factor levels is repeated several times (e.g., 128 or even 256 trials) would allow for greater assessment of the reliability of observed effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Examining two-way interactions within a task that could potentially contain five-way interactions can be seen as a compromise between these conflicting needs for parsimony and precision. Thus, future studies should work to determine if the presently observed two-way interactions within APRT are robust and of practically meaningful effect size, as the degree to which these interactions represent large enough real-world effects requires further investigation to justify the complex design of APRT [ 66 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%